"What's done is done, the bullet's left the gun": Questions on the Application, Origin, and Metaphysics of the «Course-of-Experience Framework». (April 2023) - Høffding, Simon
The Course-of-Experience presents an interesting method for working with others' experience, drawing on Micro-phenomenology (MP), Enactivism, and Peircean semiotics. It addresses possible applications to cognitive science, answering to a call about how to reliably integrate phenomenological data and experimental methods. I applaud the ambitious framework presented in the target paper, and hope that Poizat and colleagues in response or in later work will address three potential shortcoming: (1) How does the framework fare in comparison to similar methods. (2) Why is Peircean semiotics necessary for the framework? 3) Does it need to copy what seems to be epistemological and metaphysical infelicities concerning pre-reflective experience directly from MP?